Beyond local history the case of Sulu history in national persepctive - Tan, Samuel K. (2008)
As I see it, one of the enduring legacies of the Centennial celebration of the Declaration of Philippine Independence in 1998 was its significant influence on national consciousness and the integration of the series of oral, local and/or regional history conferences, seminar-workshops, exhibits and other historical and socio-cultural activities supported and funded by the Philippine Centennial Commission (PCC). The series was pursued through a Centennial project on the National Historical Institute (NHI) which received from the PCC P15-M for the reconstitution of its historical museum and its series of workshop-seminars and related activities as part of the Centennial celebration. In turn, the NHI tapped the expertise and services of two prominent national historical organizations to help conceptualize, plan, implement, coordinate and promote the rationale, goals, ideals, and outputs of the series throughout the country from Batanes to Tawi-Tawi. The Philippine National Historical Society (PNHS), which conducted 16 conferences and workshop-seminars in key cities, municipalities and centers throughout the Centennial year came out, among other outputs, with the impressive 16-volume History from the People in 1998 and 1999. The Philippine Historical Association (PHA), for its part, opted to show, through local museum exhibits and related cultural activities in chosen local areas, the importance of the Centennial celebration.